Propuesta de un modelo pedagógico y su correspondiente modelo curricular orientados al desarrollo regional - Moya Obeso, Alberto Santiago (2007)
This research tries to answer the question Wich and why will the main purpose and pedagogical axes of a Pedagogical Curricular/ Model oriented to the solution of the educational problems and the development of the region be?. From the study of the megatendencies of the world society, as well as from the necessity to form new creative generations of sciencie and technology for the regional development and the existence of an educational system in the region/country which is underdeveloping the minds of our students, it arises the necessity of an education to form human beings able to reach the highest levels of thought. Therefore , the Pedagogical/Curricular Model that we postulate aims at potentiating the processes of the thought(basic intellectual operations) in accordance with each Piagetain development stage, from the Initial Education(Cradle) to the end of the Secundary Education, articulating these stages with the central pedagogical axes of deep understanding, creativity, criticism and values. The Pedagogical/Curricular Model has as supports the study of the megatendencies of the world society, a theory of the processes of the thought wich claims that these are ontogenetically structured in a close relation to the school and a theory of the informatic technology that takes into account its potentialities for the formation of the students, as well as its riske . Therefore, this last theory has to be incorporated within the Pedagogical /Curricular Model. Methodologically , to carry out this research the regional and national reality, especially the Educational Private Center “PAIAN: LA CASA DEL SABER” were used as empirical reference , by carrying out a Bibliographical Research, the Action Research and a Theoretical and Empirical Contrast. From the conjunction of all of these ,we obtained the results, especially the Proposal of the Pedagogical/Curricular Model